2019
DOI: 10.1016/j.idairyj.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sensory evaluation indices of Cheddar cheese texture by fluorescence fingerprint measurement coupled with an optical fibre

Abstract: A fluorescence fingerprint (FF) was used to develop a quick and non-contact practical method for predicting the sensory evaluation index of cheese texture (cheese body measurement). A partial least-squares (PLS) model was constructed from FF data and cheese body measurements of Cheddar cheeses. The cheese body measurement was successfully predicted by the PLS model with a coefficient of determination for calibration of 0.800. Notably, the reproducibility of the prediction value and the model accuracy were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The regression coefficients of the calibration model were indexed to determine which Ex/Em wavelengths contributed positively or negatively to the regression model of the target variable. Moreover, the variable of importance projection (VIP) values greater than 1 were regarded as important to the estimation of the response variable [ 9 , 22 ]. The workflow of this study is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regression coefficients of the calibration model were indexed to determine which Ex/Em wavelengths contributed positively or negatively to the regression model of the target variable. Moreover, the variable of importance projection (VIP) values greater than 1 were regarded as important to the estimation of the response variable [ 9 , 22 ]. The workflow of this study is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, multidimensional fluorescence has been used to detect metabolites in biological samples to evaluate the quality of various animal products [9][10][11][12]. Multidimensional fluorescence is comprehensive, has a high sensitivity, and requires minimal sample preparation steps.…”
Section: Introductionmentioning
confidence: 99%